2003
DOI: 10.1097/01.chi.0000046833.09750.91
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Roots of Early Sexual Debut Among Adolescents in Psychiatric Care

Abstract: Objective: To identify the most important social and personal characteristics related to early sexual debut among troubled teenagers. Method:One hundred ninety-eight youths aged 12-19 years were recruited from outpatient mental health clinics and completed self-reports and interviews about their age of sexual debut; family, peer, and partner relationships (e.g., parental hostile control, negative peer influence, need for intimacy); and personal characteristics (e.g., achievement motivation, externalizing probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 94 publications
8
73
1
Order By: Relevance
“…Consistent with earlier reports (Brown, Danovsky, et al, 1997;Donenberg, Bryant, Emerson, Wilson, & Pasch, 2003), teens reported high rates of sexual behavior; 40% reported ever having vaginal, anal, and/or oral sex. Youths reported a range from 0 to 5 sexual partners in the past 3 months (M = .48; SD = .90).…”
Section: Preliminary Analysessupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with earlier reports (Brown, Danovsky, et al, 1997;Donenberg, Bryant, Emerson, Wilson, & Pasch, 2003), teens reported high rates of sexual behavior; 40% reported ever having vaginal, anal, and/or oral sex. Youths reported a range from 0 to 5 sexual partners in the past 3 months (M = .48; SD = .90).…”
Section: Preliminary Analysessupporting
confidence: 79%
“…Psychological characteristics (e.g., low self-esteem, poor affect regulation, fear of rejection, need for intimacy, poor impulse control) may play a larger role in determining risk behavior for these youths than factors like information and motivation. Hence, in addition to cognitive-behavioral mechanisms, sexual risk taking among youths in psychiatric care may be explained more fully by social and personal factors such as parental monitoring, parental permissiveness and control, parental directiveness, peer influence, and concerns about relationship intimacy (Donenberg et al, 2002;Donenberg et al, 2003). Donenberg et al (2001) found evidence for these important factors.…”
Section: Discussionmentioning
confidence: 99%
“…Effective parent-child communication about sex is positively associated with delayed sexual initiation, as well as condom use Adu-Mireku, 2003;Lieberman, 2006;Atienzo et al, 2009). This influence on adolescent sexual development and sexual socialization indicates that parents thus play an important role in the prevention of risky sexual behavior among their children (Perrino et al, 2000) and the promotion of adolescent sexual health (Donenberg et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Parental involvement and low-risk contexts are perhaps especially important for troubled youths to avoid health-compromising situations. Effective parental monitoring and positive peer influences (Donenberg et al, 2003) can play critical roles in reducing exposure to risky situations that require skills yet to develop in troubled teens. Findings from this study underscore the importance of substance use above and beyond the impact of peers and parents in HIV/AIDS risk, highlighting the importance of substance use as an additional target of HIV prevention programs for this population.…”
Section: Discussionmentioning
confidence: 99%